Effects of Ni diffusion on the accelerated conductivity degradation of scandia-stabilized zirconia films under a reducing atmosphere. Issue 7 (June 2016) - Yun, Kyong Sik; Kwon, Young-il; Kim, Jung-Hwa; Jo, Sangyoung; Yoo, Chung-Yul; Yu, Ji Haeng; Joo, Jong Hoon
Abstract: Due to the importance of Ni diffusion into the electrolyte of a solid oxide fuel cell (SOFC) during the co-sintering process, we have studied the effects of Ni diffusion on the conductivity degradation and phase change of ceria-doped scandia-stabilized zirconia (ScSZ) films. To fabricate Ni-diffused ScSZ films, ScSZ tapes have been sintered by placing porous NiO plates on both sides of the tape at 1450 °C for 10 h. The time-dependent aging behavior of the Ni-diffused ScSZ film (thickness ∼27 μm) under reducing conditions has been investigated. The dissolution of Ni into the ScSZ considerably accelerates the conductivity degradation. This degradation behavior could be correlated to the phase transition promoted by Ni precipitation in the reducing atmosphere.